Wittgenstein - "Wright, George Henrik Von" (Oxford, 1982)
This is a study of Wittgenstein's life and writings. It records the reliable facts of his life and retrieves all the information still available relating to the chronology and composition of the writings.
Keywords: Wittgenstein